Callus Induction on True Shallot Seed Explant Using a Combination of BA and 2,4-D - Krisna Dharmayanti; Endang Sulistyaningsih; Rani Agustina Wulandari (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
BA and 2,4-D combination were commonly used for in vitro culture of Shallot (Allium cepa L. var agregatum 2n = 2x = 16) to induce callus, but there was no information for callus induction on shallot seed (TSS) explant. Callus could be utilized for in vitro selection and generating of genetic variation. The aims of the research was to identify the response of TSS (Trisula and Tuk Tuk) as explant and to obtain the optimum combination of BA and 2,4-D (mg.L-1): (0–0, 2–1, 2–2, 2–3, and 2–4) in callus induction. The research had been carried out in the Tissue Culture Laboratory, Faculty of Agriculture, Universitas Gadjah Mada during the year 2015-2016. Factorial treatments of variety and growth regulators were arranged in Completely Randomized Design with four replications. Data of percentage of germination, shoot height, root length, percentage of callus formation, callus weight, and chromosomes number of callus were recorded. The results showed that combination of 2 mg.L-1 BA + (1– 4) mg.L-1 2,4-D induced callus formation on TSS but inhibits shoots and roots growth. The best callus proliferation was at a concentration of 1 mg.L-1 2,4-D. Tetraploid callus chromosomes (2n = 4x = 32) was detected in Trisula grown in the 2 mg.L-1 BA + 4 mg.L-1 2,4-D, but in the Tuk Tuk callus did not detected the changing of chromosomes number.